Educação e a luta antinazifascista no Brasil: implicações para o campo dos estudos curriculares na voz de estudantes de mestrado e doutorado - Francisco Thiago Silva (Universidade Estadual de Maringá, 2023)
The prime purpose of this research is to comprehend the main implications and consequences that the rise of the extreme right wing in Brazil has had on Education, possibly in the field of curriculum studies, from the perception of master's and doctoral students who attended a discipline on Curriculum and Teacher Education, in a postgraduate program on Education, at a federal university of a Midwestern region of Brazil, in the period of 2.2022, through the application of a questionnaire with semi-structured questions. We situated the discussions on the concept of fascism in History from a bibliographical review, to then discuss the consequences of its manifestations in the educational field, especially concerning the curriculum. Preliminarily, the data showed that there might be the existence of a 'fascistised curriculum', marked by an authoritarian and mono-centered feature throughout its pedagogical architecture, besides not taking Science as core, or when it does, it disregards ancestral forms that arose from intentionally dehumanized cultures. At the same time, it is imperative to elaborate and practice, based on some assumptions, a 'critical and socially anti-capitalist and anti-Nazifascist curriculum' that has as main characteristics: to consider the different forms of democratic collaboration as a starting point in its elaboration, planning, implementation, and evaluation; to consider and respect the different ways of being, existing, and staying in each place; to repudiate any forms and manners of authoritarian and truculent decisions throughout the pedagogical process; and to develop, through teaching autonomy, countless actions of intellectual combat against discriminatory practices of all kinds: gender, sexual orientation, race/ethnicity, social class, religion, etc. These archetypes led us to confirm the ideological conception that anti-fascism and anti-capitalism are sides of the same coin and that it is possible to defeat them.